Unsupervised Segmentation of Cattle Images Using Deep Learning - Sousa, Vinícius Guardieiro; Backes, André R. (Anais do Workshop de Visão Computacional (WVC), 2021)
In this work, we used the Deep Learning (DL) architecture named U-Net to segment images containing side view cattle. We evaluated the ability of the U-Net to segment images captured with different backgrounds and from the different breeds, both acquired by us and from the Internet. Since cattle images present a more constant background than other applications, we also evaluated the performance of the U-Net when we change the numbers of convolutional blocks and filters. Results show that U-Net can be used to segment cattle images using fewer blocks and filters than traditional U-Net and that the number of blocks is more important than the total number of filters used.